Between Commitment and Compromise: The Dynamics of Nahdlatul Ulama Traditions within Minangkabau Cultural Contexts - Soibatul Aslamiah Nasution; Iswantir Iswantir; Yulda Dina Septiana; Iswandi Iswandi (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
This study examines how Nahdlatul Ulama (NU) adherents in Minangkabau negotiate and transform their religious traditions within a socio-cultural context in which NU lacks symbolic dominance. NU is widely known for integrating Islamic tradition with local culture, yet this accommodative model does not operate uniformly across regions. In Minangkabau, the supremacy of adat basandi syarak, syarak basandi Kitabullah shapes religious legitimacy and constrains the public expression of NU traditions. This qualitative field study employs an interpretive–critical paradigm, using in-depth interviews, participant observation, and document analysis in West Pasaman Regency. The findings reveal that NU religious practices are selectively enacted and symbolically moderated to preserve social harmony. NU identity is also mobilized instrumentally for social, political, and educational purposes, functioning as flexible symbolic capital. Additionally, pesantren traditions are transmitted to younger generations primarily through ethical values, leadership development, and civic engagement rather than through consistent ritual practice. These dynamics produce what this study conceptualizes as “half-hearted devotion,” a strategic form of adaptive religiosity rather than religious decline. This research contributes to studies of lived Islam and Islam Nusantara by highlighting negotiation and ambivalence as mechanisms of continuity and by recommending a balance between flexibility and efforts to sustain embodied religious traditions.